Impact of growth hormone treatment on children’s height - Nur Rochmah; Muhammad Faizi (Paediatrica Indonesiana, 2014)
Background The use of growth hormone (GH) is a routine treatment for growth hormone deficiency (GHD), small for gestational age (SGA), and Turner syndrome (TS). During the treatment, height measurement at regular intervals is a vital step to assess success. To date, there have been no previous studies on GH treatment in Dr. Soetomo Hospital, Surabaya, the referral hospital in East Indonesia. Objective To compare body height between pre- and post-growth hormone treatment in pediatric patients. Method This study was a non-randomized, pre-post clinical trial performed at Dr. Soetomo Hospital, Surabaya. The prospective cohort was accessed during January 2008-June 2013. The inclusion criteria was GH treatment for more than 3 months.Clinical data on GH treatment, including diagnosis, age, height pre-and post-treatment, height gain, duration of treatment, and parental satisfaction were collected. Two-tailed, paired T-test and Pearson’s test were used for statistical analyses. Result Nineteen patients underwent GH treatment during the study period, but only twelve patients had complete data and were included in the study. Eight subjects were female. Subjects’ meanage was 11 (range 8-15) years. Nine patients had GHD, 2 had TS, and 1 had SGA. Mean pre-treatment height was 121.05 cm, while mean post-treatment height was 130.5 cm. Mean duration of treatment was 10.5 (range 3-30) months. Mean height gain was 0.8 cm/month in GHD and SGA cases, and 0.78 cm/month for the TS cases. Eleven parents reported satisfaction with the results of GH treatment in their children. There is significant diffrent between pre- and post-treatment (P=0.001). Pearson’s correlation test (r=0.90) revealed a strong correlation between growth hormone treatment and height gain. Conclusion Growth hormone treatment has impact on heights in GH defficiency, Turner syndrome, and small for gestational age.